The enzymatic epimerization of deoxynivalenol by Devosia mutans proceeds through the formation of 3-keto-DON intermediate - Yousef I. Hassan (Nature Portfolio, 2017)
Abstract The enzymatic detoxification of deoxynivalenol (DON) is a promising mitigation strategy for addressing this mycotoxin contamination of cereal grains. A recently described bacterium, Devosia mutans 17-2-E-8, capable of transforming DON into its non-toxic stereoisomer 3-epi-DON, holds promise for the development of such applications. Earlier observations suggested that DON epimerization proceeds via a two-step catalysis with 3-keto-DON as an intermediate. The results of this study indicate that NADPH is required for DON epimerization by cell-free protein extracts of D. mutans, while high concentrations of glucose and sucrose have a suppressive effect. Chemically synthesized 3-keto-DON incubated with D. mutans protein fractions enriched by ammonium sulfate precipitation at 35–55% saturation selectively reduced 3-keto-DON to 3-epi-DON, but fell short of supporting the complete epimerization of DON. In addition, seven Devosia species investigated for DON epimerization were all able to reduce 3-keto-DON to 3-epi-DON, but only a few were capable of epimerizing DON. The above observations collectively confirm that the enzymes responsible for the oxidation of DON to 3-keto-DON are physically separate from those involved in 3-keto-DON reduction to 3-epi-DON. The enzymatic nature of DON epimerization suggests that the process could be used to develop genetically engineered crops or microorganisms, ultimately reducing foodborne exposure of consumers and farm animals to DON.